Pengaruh Lingkungan Sekolah terhadap Kemampuan Literasi Matematika Siswa Indonesia Berdasarkan PISA 2018 - Zulfiki Hidayat; Nurwati Djam’an; Fajar Arwadi (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
This research aims to know the effect of school climate on Indonesian Students’ mathematical literacy skills based on PISA 2018. This research is a causal-comparative research. The population in this research were all 12098 Indonesian students who took part in the 2018 PISA survey. The data was collected by literature study technique. The data were analyzed with regression analysis. The results showed that there was a significant effect between the variables of bullying, student truancy and lateness, competition, co-operation, and sense of belonging at school separately on mathematical literacy skills. As for the variables of teacher behavior and parental participation, both separately do not have a significant effect on mathematical literacy skills. The school climate as a whole has a significant effect on Indonesian students’ mathematical literacy skills based on PISA 2018.